2003
DOI: 10.1103/physrevb.68.153302
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies in the NMR of silicon:  Unexpected spin echoes in a dilute dipolar solid

Abstract: NMR spin echo measurements of 29 Si in Silicon powders have uncovered a variety of surprising phenomena that appear to be independent of doping. These surprises include long tails and even-odd asymmetry in Carr-Purcell-Meiboom-Gill (CPMG) echo trains, and anomalous stimulated echoes with several peculiar characteristics. Given the simplicity of this spin system, these results, which to date defy explanation, present a new and interesting puzzle in solid state NMR.PACS numbers: 03.65. Yz, 03.67.Lx, 76.20.+q, 76… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 33 publications
9
64
0
Order By: Relevance
“…Similar situations were observed in all the systems that manifest long decay times when CPMG-like sequences are applied [12,43,44].…”
Section: Controlled Generation Of Pseudocoherencesmentioning
confidence: 51%
See 4 more Smart Citations
“…Similar situations were observed in all the systems that manifest long decay times when CPMG-like sequences are applied [12,43,44].…”
Section: Controlled Generation Of Pseudocoherencesmentioning
confidence: 51%
“…We found that, by applying the CPMG1 sequence or the CP2 sequence, a magnetization tail appears, i.e. the signal remains for times much longer than T HE 2 as observed in 29 Si [12]. Figure 1 shows the normalized magnetizations acquired by applying the sequences HE, CP1, CP2, CPMG1 and CPMG2 to polycrystalline C 60 .…”
Section: Long-lived Signalsmentioning
confidence: 99%
See 3 more Smart Citations